Factors affecting consumer intentions and decisions to purchase OCOP products: Exploring the role of pride in local specialties - Thi Lan Le; Quang Hieu Le; Duy Hung Pha (Decision Science Letters)
The purpose of the study is to identify factors affecting consumers' intention and decision to purchase OCOP products as well as to test the impact of intention to purchase OCOP products on Vietnamese consumers' decision to purchase OCOP products through a case study in Thanh Hoa province. This study uses a combination of qualitative and quantitative research methods. Qualitative research aims to test the reasonableness of each scale and screen observed variables. Quantitative research methods are used through the collection and processing of data from 250 consumers who have purchased OCOP products. Data are collected, processed and analyzed using PLS-SEM software. Based on the use of TAM consumer behavior theory and the development of 4P marketing elements to build a research model. The study added the fifth P, Pride in Local Specialties, as a new factor to match the characteristics of OCOP products. The results of the study showed that the factors: (1) Pride in Local Specialties; (2) Product Awareness; (3) Price Perception; (4) Convenience in Shopping and (5) Product Communication all have a positive impact on consumers' intention to buy OCOP products. The results of the study also showed that the intention to choose OCOP products (INT) has a great impact on consumers' decision to choose OCOP products (DEC).